2006
DOI: 10.1191/0961203306lu2306rr
|View full text |Cite
|
Sign up to set email alerts
|

The renin-angiotensin system in lupus: physiology, genes and practice, in animals and humans

Abstract: Although multiple studies suggest a potential role for angiotensin II in inflammation, most were performed either in vitro or in animals with non-immune-complex-mediated diseases. Extrapolation of these findings to humans, particularly patients with lupus, which involves multiple immunoregulatory pathways, is unclear. In autoimmune-prone MRL/lpr mice, angiotensin-converting-enzyme (ACE) inhibition improved survival although to a lesser degree than cyclophosphamide and diminished the glomerular histopathologic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 66 publications
0
15
0
Order By: Relevance
“…An animal study has highlighted the inflammatory components of the RAAS and the potential benefits of RAAS blockade in eliminating the inflammation in lupus nephritis [13]. Moreover, de Albuquerque et al [14] treated lupus-prone mice with captopril and found that captopril delayed the onset of proteinuria when administered to prenephritic mice and slowed the progression of the disease in mice with early and advanced lupus nephritis, but they did not observe any of these results in a control group treated with verapamil.…”
Section: Class I and Class Ii (Isn/rps) Lupus Nephritismentioning
confidence: 96%
“…An animal study has highlighted the inflammatory components of the RAAS and the potential benefits of RAAS blockade in eliminating the inflammation in lupus nephritis [13]. Moreover, de Albuquerque et al [14] treated lupus-prone mice with captopril and found that captopril delayed the onset of proteinuria when administered to prenephritic mice and slowed the progression of the disease in mice with early and advanced lupus nephritis, but they did not observe any of these results in a control group treated with verapamil.…”
Section: Class I and Class Ii (Isn/rps) Lupus Nephritismentioning
confidence: 96%
“…A number of animal studies have highlighted the inflammatory components of the RAAS and the potential benefits of RAAS blockade in reducing or eliminating this inflammation in lupus nephritis. 14 De Albuquerque et al 15 treated lupus-prone mice with captopril and found that captopril delays the onset of proteinuria when administered to prenephritic mice and slows progression of disease in mice with early and advanced lupus nephritis. These results were not seen in a control group treated with verapamil.…”
Section: Conservative Nonimmunomodulatory Therapy Is Appropriate Formentioning
confidence: 99%
“…Patients with SLE are often treated with blockers of the renin-angiotensin system (RAS) to control blood pressure and reduce proteinuria; however, there is conflicting evidence as to whether angiotensin-converting enzyme inhibition improves renal histopathology during SLE. Although RAS blockade is generally effective for lowering pressure in patients with SLE and can lower the risk of vascular events (36), additional antihypertensive therapies are often required to achieve adequate blood pressure control (54). In addition, there are rare cases in which RAS blockade can cause or exacerbate SLE (4,42).…”
mentioning
confidence: 99%